2004
DOI: 10.1124/mol.104.003533
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Kinase C Inhibitor Go6976 [12-(2-Cyanoethyl)-6,7,12,13-tetrahydro-13-methyl-5-oxo-5H-indolo(2,3-a)pyrrolo(3,4-c)-carbazole] Potentiates Agonist-Induced Mitogen-Activated Protein Kinase Activation through Tyrosine Phosphorylation of the Epidermal Growth Factor Receptor

Abstract: Protein kinase C (PKC) isoforms are important transducers of signals from G protein-coupled receptors (GPCRs) to diverse cellular targets, including extracellular signal-regulated kinases 1 and 2 (ERK1/2). Clone 9 rat hepatocytes (C9 cells) express receptors for angiotensin II (Ang II) type 1, lysophosphatidic acid (LPA), and epidermal growth factor (EGF), and their stimulation causes transient ERK1/2 phosphorylation through transactivation of the epidermal growth factor receptor (EGF-R). Inhibition of PKC by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
1
12
1
Order By: Relevance
“…Our results were also consistent with the reports showing that activation of EGFR and PDGFR lead to COX-2 expression in various cell types (17,56,57). Gö6976 has been shown to enhance agonist-induced tyrosine phosphorylation of the EGFR, possibly through inhibition of PTP, since a PTP inhibitor, sodium orthovanadate, mimicked the effects of Gö6976 (49). Moreover, in HTSMCs, we found that pretreatment with sodium orthovanadate, but not Gö6976, markedly enhanced CSE-regulated EGFR or PDGFR phosphorylation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results were also consistent with the reports showing that activation of EGFR and PDGFR lead to COX-2 expression in various cell types (17,56,57). Gö6976 has been shown to enhance agonist-induced tyrosine phosphorylation of the EGFR, possibly through inhibition of PTP, since a PTP inhibitor, sodium orthovanadate, mimicked the effects of Gö6976 (49). Moreover, in HTSMCs, we found that pretreatment with sodium orthovanadate, but not Gö6976, markedly enhanced CSE-regulated EGFR or PDGFR phosphorylation.…”
Section: Discussionsupporting
confidence: 94%
“…There was no change in the level of COX-1 in these cells. Gö6976 has been shown to enhance agonist-induced tyrosine phosphorylation of the EGFreceptor, possibly through inhibition of protein tyrosine phosphatase (PTP), since a PTP inhibitor, sodium orthovanadate, mimicked the effects of Gö6976 (49). We found that pretreatment with 10 M sodium orthovanadate markedly enhanced CSE-regulated COX-2 expression (Fig.…”
Section: Requirement Of Pkc␣ For Cse-induced Cox-2 Expressionmentioning
confidence: 49%
“…These findings demonstrate that both PLC and PKC can have negative regulatory roles in Ang II-induced ERK1/2 phosphorylation in fetal cardiomyocytes, in contrast to previous reports in newborn and adult cardiomyocytes (7,13,16). These observations are consistent with a previous report on the ability of Gö6976 w12-(2-cyanoethyl)-6,7,12,13-tetrahydro-13-methyl-5-oxo-5H-indolo (2,3-a)pyrrolo(3,4-c) carbazolex, another PKC inhibitor, to potentiate agonist-induced ERK1/2 phosphorylation (20). These findings reflect the ability of conventional PLCs and PKCs to mediate feedback inhibition of G-protein-coupled receptor-induced ERK1/2 activation.…”
Section: Plc and Pkc Negatively Mediate Ang Ii-induced Erk1/2 Phosphocontrasting
confidence: 49%
“…They were found to activate growth factor signalling cascades via additional mechanisms involving receptor tyrosine kinases phosphorylation, which is illustrated by various studies that have shown a cross-talk between GPCRs and EGFR. This was found to involve metalloprotease-mediated release of membrane-bound EGFR ligands that subsequently activate the EGFR, in a process called transactivation [18][19][20]. This transactivation of the EGFR via GPCR results in cellular activity such as proliferation and migration.…”
Section: Introductionmentioning
confidence: 96%